Time averaging on a shallow subtropical shelf: the search for a taphomomic clock - Barbour-Wood, S. L.; Krause R.A, Jr.; Kowalewski, M.; Wehmiller, J. F.; Simoes, M. G. (Geological Society of America, Abstracts with Programs, 2004)
36(2):134
id: 719